2013
DOI: 10.3892/or.2013.2613
|View full text |Cite
|
Sign up to set email alerts
|

A novel chemopreventive mechanism of selenomethionine: Enhancement of APE1 enzyme activity via a Gadd45a, PCNA and APE1 protein complex that regulates p53-mediated base excision repair

Abstract: Organic selenium compounds have been documented to play a role in cancer prevention. Our previous study showed that selenomethionine (SeMet) induces p53 activation without genotoxic effects including apoptosis and cell cycle arrest. In this study, we investigated the mechanism by which organic selenium compounds promote p53-mediated base excision repair (BER) activity. Our data demonstrated for the first time that the interaction between growth arrest and DNA damage-inducible protein 45A (Gadd45a), which is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 32 publications
0
15
1
Order By: Relevance
“…PCNA is a DNA repair protein that stimulates DNA excision repair 37 . When cells are exposed to a genotoxic environment, GADD45A is activated which led to enforcement G2/M checkpoint thereby providing time for DNA repair 38 ; further, the activated GADD45A promotes DNA repair via interaction with PCNA and apurinic/apyrimidinic endonuclease (APE1) as a chemopreventive mechanism 39 . Here, we showed that PCNA was elevated together with GADD45A by TMZ, thus suggesting that GADD45A promoted cell survival and protected cells from TMZ treatment through interaction with PCNA to enhance DNA repair.…”
Section: Discussionmentioning
confidence: 99%
“…PCNA is a DNA repair protein that stimulates DNA excision repair 37 . When cells are exposed to a genotoxic environment, GADD45A is activated which led to enforcement G2/M checkpoint thereby providing time for DNA repair 38 ; further, the activated GADD45A promotes DNA repair via interaction with PCNA and apurinic/apyrimidinic endonuclease (APE1) as a chemopreventive mechanism 39 . Here, we showed that PCNA was elevated together with GADD45A by TMZ, thus suggesting that GADD45A promoted cell survival and protected cells from TMZ treatment through interaction with PCNA to enhance DNA repair.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the base excision repair (BER) activity was induced and accompanied by the upregulation of p53 and PCNA in human colon cancer cell lines treated with the naturally occurring selenomethionine. The mechanism is p53-dependent and requires the binding of Gadd45a with PCNA and the endonuclease APE1/Ref-1 [59]. Gadd45a, the growth arrest and DNA-damage-inducible protein 45A, is one of the p53-activated downstream genes [60].…”
Section: Discussionmentioning
confidence: 99%
“…PCNA could have a role in BER through interaction with APE1 in the nucleus . A recent study suggested that an alternative chemopreventive mechanism of organic selenium, in which the p53 downstream gene GADD45A is activated, and this promotes BER through increased interaction of GADD45A with PCNA and APE1 . When DNA damage is present, it is sensed by DNA damage response pathways and the damage is removed through an array of DNA repair pathways.…”
Section: Discussionmentioning
confidence: 99%
“…DNA damage sensors activate signaling pathways and, hence, downstream cellular targets that alter gene expression delay the cell cycle, modify DNA repair activity and/or activate apoptosis . PCNA and APE1 might act in the first phase of the response against DNA damage, as both proteins are known to be associated with the activation of BER …”
Section: Discussionmentioning
confidence: 99%